Enhancing anti-neuroinflammation effect of X-ray-triggered RuFe-based metal-organic framework with dual enzyme-like activities - Chen, Shurui; Gao, Jinpeng; Lin, Sen; Zhao, Haosen (Frontiers in Bioengineering and Biotechnology, 2024)
Traumatic spinal cord injury (SCI), often resulting from external physical trauma, initiates a series of complex pathophysiological cascades, with severe cases leading to paralysis and presenting significant clinical challenges. Traditional diagnostic and therapeutic approaches, particularly X-ray imaging, are prevalent in clinical practice, yet the limited efficacy and notable side effects of pharmacological treatments at the injury site continue to pose substantial hurdles. Addressing these challenges, recent advancements have been made in the development of multifunctional nanotechnology and synergistic therapies, enhancing both the efficacy and safety of radiographic techniques. In this context, we have developed an innovative nerve regeneration and neuroprotection nanoplatform utilizing an X-ray-triggered, on-demand RuFe metal-organic framework (P-RuFe) for SCI recovery. This platform is designed to simulate the enzymatic activities of catalase and superoxide dismutase, effectively reducing the production of reactive oxygen species, and to remove free radicals and reactive nitrogen species, thereby protecting cells from oxidative stress-induced damage. In vivo studies have shown that the combination of P-RuFe and X-ray treatment significantly reduces mortality in SCI mouse models and promotes spinal cord repair by inhibiting glial cell proliferation and neuroinflammation. P-RuFe demonstrates excellent potential as a safe, effective scavenger of reactive oxygen and nitrogen species, offering good stability, biocompatibility, and high catalytic activity, and thus holds promise for the treatment of inflammation-related diseases.